KONSEKUENSI PENETAPAN AWAL KEHIDUPAN MANUSIA TERHADAP PENERAPAN KETENTUAN HUKUM PIDANA - Hanafiah Hanafiah (Masalah-Masalah Hukum, 2013)
Determination of early human life in the womb of a woman is an urgent as it relates to criminal action (Jarimah) one does. The Indonesian Criminal Code {Their Code) does not discuss when a fetus in the womb of a woman staring to be called as a living man. The issues of when the spirit breathed by God to the human being and human esxistance by the natural processes (medical) are two concepts faced by the Islamic scholars to establish a foothold of the early human life. The Islamic scholars agreed that if the soul has been breathed against aborting fetuses is unlawful and the subject must pay "kaffarat". While the fetus is not yet breathed the spirit, there is a different of opinion; some consider "makruh" and some allow it.